Comparative analysis of fixed and sun tracking low power PV systems considering energy consumption. (1st March 2015) - Lazaroiu, George Cristian; Longo, Michela; Roscia, Mariacristina; Pagano, Mario
Highlights: Photovoltaic system prototype with sun tracking. Energy analysis of fixed and sun tracking built prototypes. Experimental tests in different environmental conditions. Theoretical and experimental validation of the prototype. Abstract: Photovoltaic technology allows to directly convert solar energy into electrical energy with clear advantages: no environmental impact during operation, reliability and durability of the systems, reduced operating costs and maintenance, ability to both supply remote customers and simply connect to the electrical network. This paper evaluates the performance of two photovoltaic systems: one fixed and one equipped with a sun tracker. The objective of this research is to analyze the increase of daily produced energy by using the sun tracking system. The analysis accounts also the energy consumption of the sun tracker. An analytical approach is proposed. To validate the results through experimental tests, two alternative low power PV systems were built. Each system consists of a PV source, a MPPT (Maximum Power Point Tracker) power converter and a 12 V–40 A h electrochemical battery, which is used as electric load. The sun tracker system evidenced an important growth of power production during morning and evening.